A method for preparing electrode foil for low-defect and high-capacity aluminum electrolytic capacitor

By using multi-stage transformation treatment, pulse cleaning and decomposition into polyethylene glycol glycidyl dodecyl ether in the repair solution during the preparation of electrode foil of aluminum electrolytic capacitors, the hydrated alumina increases the thickness of the oxide film and produces defects. The problem is that low defects and high specific capacitance electrode foil performance is achieved.

CN119170417BActive Publication Date: 2025-02-25NANTONG HAIXING ELECTRONICS +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411659057.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The hydrated alumina generated by the aluminum electrolytic capacitor during the anodic oxidation production process increases the thickness of the oxide film, reduces the capacity, and is prone to defects, affecting the performance of the electrode foil.

Method used

A method of preparation of electrode foil for low defect high capacity aluminum electrolytic capacitors, including pickling, pulse cleaning, boiling treatment, multi-stage transformation treatment, heat treatment, melting treatment and passivation, etc., through two pulse treatments and Polyethylene glycol glycidyl dodecyl ether is added to the repair solution to remove the hydrated alumina film and improve the density of the oxide film.

Benefits of technology

It effectively reduces the leakage current of the electrode foil, improves the specific capacitance, reduces defects, and improves the overall performance and quality of the electrode foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of manufacturing electrode foil for aluminum electrolytic capacitors, and specifically to a method for preparing electrode foil for low-defect and high-capacity aluminum electrolytic capacitors. The method for preparing electrode foil for low-defect and high-capacity aluminum electrolytic capacitors of the present invention comprises the following steps: (1) pickling, (2) first pulse treatment, (3) chemical formation treatment, (4) heat treatment, (5) second pulse cleaning, (6) chemical formation repair treatment, and (7) passivation. The electrode foil for low-defect and high-capacity aluminum electrolytic capacitors of the present invention removes the hydrated aluminum oxide film generated on the surface of the corroded foil in the air and the hydrated aluminum oxide film produced in the chemical formation process by pulse laser cleaning, and performs oxide film repair in a chemical formation repair solution, thereby promoting the formation of a high-crystallinity anodized film, reducing defects, and improving density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of manufacturing electrode foil for aluminum electrolytic capacitors, and in particular to a method for preparing electrode foil for low-defect and high-capacity aluminum electrolytic capacitors. Background Art

[0002] In recent years, the consumer electronics market has shown a clear upward trend. The demand for aluminum electrolytic capacitors in fields such as big data servers, new energy, and industrial control has continued to rise. In particular, in fields such as smartphones, wearable devices, and automotive, higher requirements have been placed on the miniaturization and safety of aluminum electrolytic capacitors. Electrode foil is the core raw material of aluminum electrolytic capacitors. Improving the specific capacitance of electrode foil and reducing defects have become hot research issues.

[0003] Patent technology document CN113322454B discloses a method for forming a low-pressure chemical foil and the low-pressure chemical foil obtained. The chemical method of the invention includes the following steps: S1. placing the aluminum foil in a 3-15wt% aqueous solution of adipic acid salt for the first stage of chemical formation and the first water washing; S2. subjecting the aluminum foil after the first water washing in S1 to phosphoric acid passivation treatment, and then to heat treatment, the heat treatment temperature is 300-550℃, the time is 1-5min, and then to water washing for the second time; S3. placing the aluminum foil after the second water washing in S2 in a 0.01-0.1wt.% aqueous solution of phosphoric acid for the second stage of chemical formation, taking it out, and then washing it for the third time and drying it to obtain the low-pressure chemical foil. Through the chemical formation method of the present invention, the aluminum foil is formed in an adipic acid salt aqueous solution, washed with water, passivated in a phosphoric acid solution, and then heat treated and phosphorylated at a low concentration, and the leakage current of the obtained low-pressure chemical foil is ≤14μF / cm 2 , which can effectively improve product stability and extend the service life of low-voltage aluminum electrolytic capacitors. However, during the anodizing process of the electrode foil, in addition to generating γ-Al2O3 with good dielectric properties, it will also generate hydrated alumina that does not have dielectric properties. On the one hand, hydrated alumina increases the overall thickness of the oxide film and reduces the capacity. On the other hand, hydrated alumina is also prone to more defects. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity, so as to provide an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity.

[0005] Based on the above purpose, the present invention provides a method for preparing an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor, comprising the following steps:

[0006] S1: The etched foil is pickled and then subjected to the first pulse cleaning;

[0007] S2: The corroded foil obtained in step (1) is boiled, and then sequentially subjected to primary chemical treatment, secondary chemical treatment, tertiary chemical treatment, quaternary chemical treatment, and quintuple chemical treatment.

[0008] S3: heat treating the aluminum foil after the chemical treatment, and then performing a second pulse cleaning;

[0009] S4: placing the formed foil obtained in step (3) in a forming repair solution for forming repair treatment, followed by passivation to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0010] Preferably, the thickness of the etching foil in step S1 is 130 μm.

[0011] Preferably, the pulse frequency of the pulse cleaning in step S1 is 3 kHz, the average power is 50 W, and the scanning speed is 1000 mm / s, the purpose of which is to remove the hydrated aluminum oxide film on the surface of the corrosion foil in the air environment.

[0012] Preferably, the pulse frequency of the pulse cleaning in step S3 is 2 kHz, the average power is 100 W, and the scanning speed is 1500 mm / s, the purpose of which is to remove the externally generated hydrated oxide film during the anodizing process and the defective oxide film after heat treatment.

[0013] Preferably, the pulse cleaning in steps S1 and S3 uses a nanosecond pulse fiber laser.

[0014] Preferably, the chemical repair liquid in step S4 is composed of 10%-12% by mass of boric acid, 1%-1.5% by mass of ammonium pentaborate solution, and 0.5%-1% by mass of organic acid and 0.1%-0.5% by mass of polyethylene glycol glycidyl dodecyl ether.

[0015] Preferably, the organic acid is one of acetic acid, benzoic acid, adipic acid and malic acid.

[0016] Preferably, the pickling in step S1 is performed in a 60-150 g / L sulfuric acid solution at 40-60° C. for 1-3 min, the purpose of which is to remove organic matter and grease on the surface of the corroded foil.

[0017] Preferably, the boiling treatment in step S2 is boiling in boiling water at 90-98° C. for 8-10 minutes.

[0018] Preferably, the primary formation liquid is 2%-10% boric acid and 0.5%-2% ammonium citrate solution, and the formation conditions are: temperature 70-90°C, current density 10-20 mA / cm 2, voltage is 190V, time is 10-20min.

[0019] Preferably, the secondary formation solution is 2%-10% boric acid and 0.2%-1.5% ammonium citrate solution, and the formation conditions are: temperature 70-90°C, current density 10-20 mA / cm 2 , voltage is 320V, time is 10-20min.

[0020] Preferably, the three-stage formation solution is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, and the formation conditions are: temperature 80-95°C, current density 10-20 mA / cm 2 , voltage is 450V, time is 8-15 min.

[0021] Preferably, the four-stage formation solution is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, and the formation conditions are: temperature 80-95°C, current density 10-20 mA / cm 2 , voltage is 600V, time is 20-30 min.

[0022] Preferably, the five-stage formation solution is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, and the formation conditions are: temperature 80-95°C, current density 10-20 mA / cm 2 , voltage is 640V, time is 20-30 min.

[0023] Preferably, the heat treatment in step S3 is performed at a temperature of 400-500° C. and for a time of 3 minutes.

[0024] Preferably, the passivation in step S4 is performed by immersing in a 1%-5% diammonium dihydrogen phosphate solution at 60-80° C. for 5-10 min.

[0025] Beneficial effects of the present invention:

[0026] The invention adds polyethylene glycol glycidyl dodecyl ether into the chemical repair liquid, so that the oxide film formed on the surface of the chemical foil is more compact and uniform, and compared with the commonly used surfactant sodium dodecyl sulfate, the invention can further reduce the leakage current of the aluminum foil and improve the specific capacity.

[0027] The present invention adds two pulse treatments in the chemical formation process, so that the hydrated aluminum oxide film generated on the surface of the corrosion foil in the air and the hydrated aluminum oxide film produced in the chemical formation process are removed, the specific surface area is increased, and the specific volume of the electrode foil is improved, local defects are reduced, and leakage current is reduced.

[0028] The present invention adds two pulse treatments in the chemical formation process and adds polyethylene glycol glycidyl dodecyl ether to the chemical formation repair liquid, which together make the oxide film on the surface of the electrode foil smaller in defects, more uniform, and more dense, and the final electrode foil has better performance and better quality. DETAILED DESCRIPTION

[0029] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0030] The polyethylene glycol glycidyl dodecyl ether used in the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the product number of P304797.

[0031] Example 1: An electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0032] (1) A 130 μm thick corroded foil was immersed in a 60 g / L sulfuric acid solution at 40 °C for 1 min, taken out and rinsed with water, and then pulse-cleaned using a nanosecond pulse fiber laser. The nanosecond pulse fiber laser had a pulse frequency of 3 kHz, an average power of 50 W, and a scanning speed of 1000 mm / s.

[0033] (2) boiling the corroded foil obtained in step (1) in 90° C. water for 8 min, then washing and draining;

[0034] (3) The corroded foil obtained in step (2) was placed in a 2% boric acid and 0.5% ammonium citrate solution at 70°C and a current density of 10 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 10min, and then taken out for washing;

[0035] (4) The foil obtained in step (3) was placed in a 2% boric acid and 0.2% ammonium citrate solution at 70°C and a current density of 10 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 10min, and then taken out for washing;

[0036] (5) The foil obtained in step (4) was placed in a 4% boric acid and 0.1% ammonium pentaborate solution at 80°C and a current density of 10 mA / cm 2 , perform three-stage formation at a voltage of 450V for 8 minutes, and then take out and wash with water;

[0037] (6) The foil obtained in step (5) was placed in a 4% boric acid and 0.1% ammonium pentaborate solution at 80°C and a current density of 10 mA / cm 2, perform four-stage formation at a voltage of 600 V, control the formation time within 20 min, and take out for water washing;

[0038] (7) The foil obtained in step (6) was placed in a 4% boric acid and 0.1% ammonium pentaborate solution at 80°C and a current density of 10 mA / cm 2 , five-stage formation is carried out at a voltage of 640V for 20min, and then the product is taken out for washing;

[0039] (8) placing the foil obtained in step (7) in an oven at 400°C for 3 min;

[0040] (9) Setting the pulse frequency of the nanosecond pulse fiber laser to 2 kHz, the average power to 100 W, and the scanning speed to 1500 mm / s, pulse cleaning the formed foil obtained in step (8);

[0041] (10) The foil obtained in step (9) was placed in a solution of 10% by mass boric acid and 1% by mass ammonium pentaborate, and 0.5% by mass acetic acid was added, followed by 0.1% by mass polyethylene glycol glycidyl dodecyl ether, and the mixture was heated at 80°C and a current density of 10 mA / cm 2 , the voltage is 640V, the formation time is 5min, and then taken out for washing;

[0042] (11) The formed foil obtained in step (10) is placed in a 1% by mass diammonium phosphate solution, immersed at 60°C for 5 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0043] Example 2: An electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0044] (1) A 130 μm thick corroded foil was immersed in a 100 g / L sulfuric acid solution at 50 °C for 2 min, taken out and rinsed with water, and then pulse-cleaned using a nanosecond pulse fiber laser. The nanosecond pulse fiber laser had a pulse frequency of 3 kHz, an average power of 50 W, and a scanning speed of 1000 mm / s.

[0045] (2) boiling the corroded foil obtained in step (1) in 94° C. water for 9 min, then washing and draining;

[0046] (3) The corroded foil obtained in step (2) was placed in a 6% boric acid and 1.5% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 15min, and then taken out for washing;

[0047] (4) The foil obtained in step (3) was placed in a 6% boric acid and 0.8% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 15min, and then taken out for washing;

[0048] (5) The foil obtained in step (4) was placed in an 8% boric acid and 0.5% ammonium pentaborate solution at 88°C and a current density of 15 mA / cm 2 , perform three-stage formation at a voltage of 450 V for 12 min, and then take out and wash with water;

[0049] (6) The foil obtained in step (5) was placed in a 10% boric acid and 0.5% ammonium pentaborate solution at 90°C and a current density of 15 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 25 min, and then take out and wash with water;

[0050] (7) The foil obtained in step (6) was placed in a 12% boric acid and 0.5% ammonium pentaborate solution and heated at 805°C and a current density of 15 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 25 min, and then the product is taken out for washing;

[0051] (8) placing the foil obtained in step (7) in an oven at 450°C for 3 min;

[0052] (9) Setting the pulse frequency of the nanosecond pulse fiber laser to 2 kHz, the average power to 100 W, and the scanning speed to 1500 mm / s, pulse cleaning the formed foil obtained in step (8);

[0053] (10) The foil obtained in step (9) was placed in a solution of 11% by mass boric acid and 1.3% by mass ammonium pentaborate, and 0.8% by mass acetic acid and 0.3% by mass polyethylene glycol glycidyl dodecyl ether were added at 87°C and a current density of 15 mA / cm 2 , the voltage is 640V, the formation time is 8min, and then taken out for washing;

[0054] (11) The formed foil obtained in step (10) is placed in a 3% by mass diammonium phosphate solution, immersed at 70° C. for 8 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0055] Example 3: An electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0056] (1) A 130 μm thick corroded foil was immersed in a 150 g / L sulfuric acid solution at 60 °C for 3 min, taken out and rinsed with water, and then pulse-cleaned using a nanosecond pulse fiber laser. The nanosecond pulse fiber laser had a pulse frequency of 3 kHz, an average power of 50 W, and a scanning speed of 1000 mm / s.

[0057] (2) boiling the corroded foil obtained in step (1) in 98°C boiling water for 10 min, then washing with water and draining;

[0058] (3) The corroded foil obtained in step (2) was placed in a 10% boric acid and 2% ammonium citrate solution at 90°C and a current density of 20 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 20min, and then taken out for washing;

[0059] (4) The foil obtained in step (3) was placed in a 10% boric acid and 1.5% ammonium citrate solution at 90°C and a current density of 20 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 20min, and then taken out for washing;

[0060] (5) The foil obtained in step (4) was placed in a 15% boric acid and 1% ammonium pentaborate solution at 95°C and a current density of 20 mA / cm 2 , perform three-stage formation at a voltage of 450 V for 15 min, and then take out and wash with water;

[0061] (6) The foil obtained in step (5) was placed in a 15% boric acid and 1% ammonium pentaborate solution at 95°C and a current density of 20 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 30 min, and then take out and wash with water;

[0062] (7) The foil obtained in step (6) was placed in a 15% boric acid and 1% ammonium pentaborate solution at 95°C and a current density of 20 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 30 min, and then the product is taken out for washing;

[0063] (8) placing the foil obtained in step (7) in an oven at 500°C for 3 min;

[0064] (9) Setting the pulse frequency of the nanosecond pulse fiber laser to 2 kHz, the average power to 100 W, and the scanning speed to 1500 mm / s, pulse cleaning the formed foil obtained in step (8);

[0065] (10) The foil obtained in step (9) was placed in a solution of 12% by mass boric acid and 1.5% by mass ammonium pentaborate, and 1% by mass acetic acid and 0.5% by mass polyethylene glycol glycidyl dodecyl ether were added at 95°C and a current density of 20 mA / cm 2 , the voltage is 640V, the formation time is 10min, and then taken out for washing;

[0066] (11) The formed foil obtained in step (10) is placed in a 5% by mass concentration diammonium phosphate solution, immersed at 80° C. for 10 min, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0067] Comparative Example 1: An electrode foil for an aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0068] The difference from Example 2 is that polyethylene glycol glycidyl dodecyl ether is replaced by sodium dodecyl sulfate. The specific steps are as follows:

[0069] (1) A 130 μm thick corroded foil was immersed in a 100 g / L sulfuric acid solution at 50 °C for 2 min, taken out and rinsed with water, and then pulse-cleaned using a nanosecond pulse fiber laser. The nanosecond pulse fiber laser had a pulse frequency of 3 kHz, an average power of 50 W, and a scanning speed of 1000 mm / s.

[0070] (2) boiling the corroded foil obtained in step (1) in 94° C. water for 9 min, then washing and draining;

[0071] (3) The corroded foil obtained in step (2) was placed in a 6% boric acid and 1.5% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 15min, and then taken out for washing;

[0072] (4) The foil obtained in step (3) was placed in a 6% boric acid and 0.8% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 15min, and then taken out for washing;

[0073] (5) The foil obtained in step (4) was placed in an 8% boric acid and 0.5% ammonium pentaborate solution at 88°C and a current density of 15 mA / cm 2 , perform three-stage formation at a voltage of 450 V for 12 min, and then take out and wash with water;

[0074] (6) The foil obtained in step (5) was placed in a 10% boric acid and 0.5% ammonium pentaborate solution at 90°C and a current density of 15 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 25 min, and then take out and wash with water;

[0075] (7) The foil obtained in step (6) was placed in a 12% boric acid and 0.5% ammonium pentaborate solution and heated at 805°C and a current density of 15 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 25 min, and then the product is taken out for washing;

[0076] (8) placing the foil obtained in step (7) in an oven at 450°C for 3 min;

[0077] (9) Setting the pulse frequency of the nanosecond pulse fiber laser to 2 kHz, the average power to 100 W, and the scanning speed to 1500 mm / s, pulse cleaning the formed foil obtained in step (8);

[0078] (10) The foil obtained in step (9) was placed in a solution of 11% by mass boric acid and 1.3% by mass ammonium pentaborate, and 0.8% by mass acetic acid and 0.3% by mass sodium dodecyl sulfate were added at 87°C and a current density of 15 mA / cm 2 , the voltage is 640V, the formation time is 8min, and then taken out for washing;

[0079] (11) The formed foil obtained in step (10) is placed in a 3% by mass diammonium phosphate solution, immersed at 70° C. for 8 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0080] Comparative Example 2: An electrode foil for an aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0081] The difference from Example 2 is that polyethylene glycol glycidyl dodecyl ether is not added, and the specific steps are as follows:

[0082] (1) A 130 μm thick corroded foil was immersed in a 100 g / L sulfuric acid solution at 50 °C for 2 min, taken out and rinsed with water, and then pulse-cleaned using a nanosecond pulse fiber laser. The nanosecond pulse fiber laser had a pulse frequency of 3 kHz, an average power of 50 W, and a scanning speed of 1000 mm / s.

[0083] (2) boiling the corroded foil obtained in step (1) in 94° C. water for 9 min, then washing and draining;

[0084] (3) The corroded foil obtained in step (2) was placed in a 6% boric acid and 1.5% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 15min, and then taken out for washing;

[0085] (4) The foil obtained in step (3) was placed in a 6% boric acid and 0.8% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 15min, and then taken out for washing;

[0086] (5) The foil obtained in step (4) was placed in an 8% boric acid and 0.5% ammonium pentaborate solution at 88°C and a current density of 15 mA / cm 2 , perform three-stage formation at a voltage of 450 V for 12 min, and then take out and wash with water;

[0087] (6) The foil obtained in step (5) was placed in a 10% boric acid and 0.5% ammonium pentaborate solution at 90°C and a current density of 15 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 25 min, and then take out and wash with water;

[0088] (7) The foil obtained in step (6) was placed in a 12% boric acid and 0.5% ammonium pentaborate solution and heated at 805°C and a current density of 15 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 25 min, and then the product is taken out for washing;

[0089] (8) placing the foil obtained in step (7) in an oven at 450°C for 3 min;

[0090] (9) Setting the pulse frequency of the nanosecond pulse fiber laser to 2 kHz, the average power to 100 W, and the scanning speed to 1500 mm / s, pulse cleaning the formed foil obtained in step (8);

[0091] (10) The foil obtained in step (9) was placed in a solution of 11% by mass boric acid and 1.3% by mass ammonium pentaborate, and 0.8% by mass acetic acid was added at 87°C and a current density of 15 mA / cm 2 , the voltage is 640V, the formation time is 8min, and then taken out for washing;

[0092] (11) The formed foil obtained in step (10) is placed in a 3% by mass diammonium phosphate solution, immersed at 70° C. for 8 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0093] Comparative Example 3: An electrode foil for an aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0094] The difference from Example 2 is that the two pulse treatments are not performed. The specific preparation steps are as follows:

[0095] (1) Immerse the 130 μm thick corrosion foil in 100 g / L sulfuric acid solution at 50 °C for 2 min, then take it out and rinse it with water;

[0096] (2) boiling the corroded foil obtained in step (1) in 94° C. water for 9 min, then washing and draining;

[0097] (3) The corroded foil obtained in step (2) was placed in a 6% boric acid and 1.5% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 15min, and then taken out for washing;

[0098] (4) The foil obtained in step (3) was placed in a 6% boric acid and 0.8% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 15min, and then taken out for washing;

[0099] (5) The foil obtained in step (4) was placed in an 8% boric acid and 0.5% ammonium pentaborate solution at 88°C and a current density of 15 mA / cm 2 , perform three-stage formation at a voltage of 450 V for 12 min, and then take out and wash with water;

[0100] (6) The foil obtained in step (5) was placed in a 10% boric acid and 0.5% ammonium pentaborate solution at 90°C and a current density of 15 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 25 min, and then take out and wash with water;

[0101] (7) The foil obtained in step (6) was placed in a 12% boric acid and 0.5% ammonium pentaborate solution and heated at 805°C and a current density of 15 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 25 min, and then the product is taken out for washing;

[0102] (8) placing the foil obtained in step (7) in an oven at 450°C for 3 min;

[0103] (9) The foil obtained in step (8) was placed in a solution of 11% by mass boric acid and 1.3% by mass ammonium pentaborate, and 0.8% by mass acetic acid and 0.3% by mass polyethylene glycol glycidyl dodecyl ether were added at 87°C and a current density of 15 mA / cm 2 , the voltage is 640V, the formation time is 8min, and then taken out for washing;

[0104] (10) The formed foil obtained in step (9) is placed in a 3% by mass ammonium dihydrogen phosphate solution, immersed at 70° C. for 8 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0105] Comparative Example 4: An electrode foil for an aluminum electrolytic capacitor, the specific preparation steps are as follows:

[0106] (1) Immerse the 130 μm thick corrosion foil in 100 g / L sulfuric acid solution at 50 °C for 2 min, then take it out and rinse it with water;

[0107] (2) boiling the corroded foil obtained in step (1) in 94° C. water for 9 min, then washing and draining;

[0108] (3) The corroded foil obtained in step (2) was placed in a 6% boric acid and 1.5% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 190V for primary formation, the formation time is 15min, and then taken out for washing;

[0109] (4) The foil obtained in step (3) was placed in a 6% boric acid and 0.8% ammonium citrate solution at 80°C and a current density of 15 mA / cm 2 , the voltage is 320V for secondary formation, the formation time is 15min, and then taken out for washing;

[0110] (5) The foil obtained in step (4) was placed in an 8% boric acid and 0.5% ammonium pentaborate solution at 88°C and a current density of 15 mA / cm 2, perform three-stage formation at a voltage of 450 V for 12 min, and then take out and wash with water;

[0111] (6) The foil obtained in step (5) was placed in a 10% boric acid and 0.5% ammonium pentaborate solution at 90°C and a current density of 15 mA / cm 2 , perform four-stage formation at a voltage of 600 V, the formation time is controlled within 25 min, and then take out and wash with water;

[0112] (7) The foil obtained in step (6) was placed in a 12% boric acid and 0.5% ammonium pentaborate solution and heated at 805°C and a current density of 15 mA / cm 2 , five-stage formation is carried out at a voltage of 640 V for 25 min, and then the product is taken out for washing;

[0113] (8) placing the foil obtained in step (7) in an oven at 450°C for 3 min;

[0114] (9) The foil obtained in step (8) was placed in a solution of 11% by mass boric acid and 1.3% by mass ammonium pentaborate, and 0.8% by mass acetic acid was added at 87°C and a current density of 15 mA / cm 2 , the voltage is 640V, the formation time is 8min, and then taken out for washing;

[0115] (10) The formed foil obtained in step (9) is placed in a 3% by mass ammonium dihydrogen phosphate solution, immersed at 70° C. for 8 minutes, taken out, washed with water, and dried to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor.

[0116] Performance Testing

[0117] Specific volume: According to the EIAJ RC-2364A standard method, the specific volume tester is used for measurement. The test results are shown in Table 1.

[0118] Withstand voltage test: Withstand voltage 640Vf, the test solution is 70g / L boric acid, the conductivity is 133.3μs / cm, the pH is 3.2, the sample is immersed in the test solution, the tested part is 6-8mm below the liquid surface, the data is read in the computer of the withstand voltage tester, when it rises to the corresponding withstand voltage value, the corresponding current is the leakage current, the test results are shown in Table 1.

[0119] Table 1 Performance test results

[0120]

[0121] Data Analysis:

[0122] It can be seen from Examples 1-3 that the electrode foil for low-defect and high-capacity aluminum electrolytic capacitors of the present invention is subjected to two pulse laser cleaning and chemical formation repair treatments, so that the final electrode foil has the characteristics of low defects and high specific capacitance.

[0123] It can be seen from Example 2 and Comparative Examples 1 and 2 that the present invention adds polyethylene glycol glycidyl dodecyl ether to the chemical repair liquid, so that the oxide film formed on the surface of the chemical foil is more compact and uniform. This may be because polyethylene glycol glycidyl dodecyl ether can be used as a surfactant to reduce the surface tension of the chemical liquid, improve the wettability of the chemical liquid on the aluminum foil surface, and improve the coverage of the chemical liquid on the aluminum foil surface, thereby improving the compactness of the oxide film; at the same time, compared with sodium dodecyl sulfate, it can improve the compatibility between boric acid and organic acid through the action of its own hydrophilic and hydrophobic groups, on the one hand, it can reduce the bubbles generated in the chemical process, and on the other hand, it controls the growth rate and uniformity of the surface oxide film, prevents local excessive thickness or thinness, reduces defects and cracks in the film, thereby improving the overall quality of the oxide film, so that the specific volume of the chemical foil is further improved, and the leakage current is further reduced.

[0124] It can be seen from Example 2 and Comparative Example 3 that the present invention adds two pulse treatments in the chemical formation process, so that the hydrated aluminum oxide film generated on the surface of the corrosion foil in the air and the hydrated aluminum oxide film produced in the chemical formation process are removed, the specific surface area is increased, and the specific volume of the electrode foil is improved, while the thickness of the overall oxide film is reduced. The pulse treatment can promote the uniform growth of the oxide film, reduce local defects, and reduce leakage current.

[0125] It can be seen from Example 2 and Comparative Example 4 that the present invention adds two pulse treatments in the chemical formation process and adds polyethylene glycol glycidyl dodecyl ether to the chemical formation repair liquid, which together make the oxide film defects on the surface of the electrode foil smaller, more uniform, and denser, and the final electrode foil has better performance and better quality.

[0126] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor, characterized in that: The following steps are involved: S1: The etched foil is pickled and then subjected to the first pulse cleaning; S2: The corroded foil obtained in step (1) is boiled and then subjected to chemical treatment: S3: heat treating the aluminum foil after the chemical treatment, and then performing a second pulse cleaning; S4: placing the formed foil obtained in step (3) in a forming repair solution for forming repair treatment, followed by passivation to obtain an electrode foil for a low-defect and high-capacity aluminum electrolytic capacitor; The pulse frequency of the pulse cleaning in step S1 is 3kHz, the average power is 50W, and the scanning speed is 1000mm / s; The pulse frequency of the pulse cleaning in step S3 is 2kHz, the average power is 100W, and the scanning speed is 1500mm / s; The pulse cleaning in steps S1 and S3 uses a nanosecond pulse fiber laser; The chemical repair solution in step S4 is composed of 10%-12% by mass of boric acid, 1%-1.5% by mass of ammonium pentaborate solution, 0.5%-1% by mass of organic acid and 0.1%-0.5% by mass of polyethylene glycol glycidyl dodecyl ether.

2. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The pickling in step S1 is performed in a 60-150 g / L sulfuric acid solution at 40-60° C. for 1-3 min.

3. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The boiling treatment in step S2 is boiling in boiling water at 90-98° C. for 8-10 minutes.

4. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The chemical formation treatment in step S2 is first-level chemical formation, second-level chemical formation, third-level chemical formation, fourth-level chemical formation, and fifth-level chemical formation in sequence.

5. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 4, characterized in that: The primary formation liquid is 2%-10% boric acid and 0.5%-2% ammonium citrate solution, and the formation conditions are: temperature 70-90°C, current density 10-20mA / cm 2 , voltage is 190V, time is 10-20min; the secondary formation liquid is 2%-10% boric acid and 0.2%-1.5% ammonium citrate solution, the formation conditions are: temperature is 70-90℃, current density is 10-20mA / cm 2 , voltage is 320V, time is 10-20min; the three-stage formation liquid is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, the formation conditions are: temperature is 80-95℃, current density is 10-20mA / cm 2 , voltage is 450V, time is 8-15 min; the four-stage formation liquid is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, the formation conditions are: temperature is 80-95℃, current density is 10-20mA / cm 2 , voltage is 600V, time is 20-30 min; the five-stage formation liquid is 4%-15% boric acid and 0.1%-1% ammonium pentaborate solution, the formation conditions are: temperature is 80-95℃, current density is 10-20mA / cm 2 , voltage is 640V, time is 20-30 min.

6. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The heat treatment in step S3 is performed at a temperature of 400-500° C. and for a time of 3 minutes.

7. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The passivation in step S4 is performed by immersing in a 1%-5% diammonium dihydrogen phosphate solution at 60-80° C. for 5-10 minutes.

8. The method for preparing an electrode foil for an aluminum electrolytic capacitor with low defects and high capacity according to claim 1, characterized in that: The organic acid is one of acetic acid, benzoic acid, adipic acid and malic acid.

Citation Information

Patent Citations

  • A method for forming a low-voltage forming foil and the resulting low-voltage forming foil

    CN113322454B

  • Production of electrolytic capacitor anode aluminum foil

    CN101030487A

  • Method for manufacturing electrode foil for aluminum electrolytic capacitor with wide temperature range, low impedance, shrinkage, large ripple current resistance and long service life

    CN113897651A